Dynamic Variability of Geostrophic Currents in the Western Sumatra Waters: Insights from Altimetry Satellite Data: Variabilitas Dinamis Arus Geostrofik di Perairan Barat Sumatera: Wawasan dari Data Satelit Altimetri - Nelva Pebryanty Regina Simbolon; Lizalidiawati Lizalidiawati; Chandra Kurniawan (Academia Open, 2023)
The Western Sumatra Waters experience significant influence from mass differentials between the Indian Ocean and Pacific Ocean, resulting in intricate oceanic circulations. This study focuses on geostrophic currents, vital for global climate dynamics, aiming to analyze their distribution and extreme occurrences. Using monthly-averaged geostrophic current data from 2018 to 2020 obtained via Altimetry Satellite imagery, the analysis reveals variations in velocity, magnitude, and direction across months. A notable peak velocity of 1.2 m/s in May 2020 and a minimum velocity of 0.1 m/s in June 2020 are highlighted, offering insights into their complex dynamics and implications for the region's oceanic processes and global climate dynamics. Highlight: Oceanic Interplay: The study highlights the profound influence of mass differentials between the Indian Ocean and Pacific Ocean on intricate oceanic circulations in the Western Sumatra Waters. Geostrophic Current Dynamics: Examining geostrophic currents as a crucial element of global climate dynamics, the research reveals significant variations in velocity, magnitude, and direction across different months. Peak and Minimum Instances: Notable instances are identified, such as the May 2020 peak with currents dispersing from west to southeast, and the June 2020 minimum characterized by erratic directional behavior, shedding light on specific temporal patterns. Keyword: Geostrophic Currents, Oceanic Circulations, Climate Dynamics, Western Sumatra Waters, Altimetry Satellite Data